Oxidation behavior and electrochemical corrosion performance of Ti₃Al alloy with TiAl coating - Yanjun Xi; Yongjun Liu; Zhixin Wang; Jinbin Lu (Фізико-хімічна механіка матеріалів, 2010)
Magnetron-sputter deposition was used to produce Ti–48Al–8Cr–2Ag (at.%) coating on a Ti–24Al–17Nb–0.5Mo (at.%) alloy substrate. Oxidation behavior was studied in air at 900...1000°C. The results indicated that the oxidation rate of sputtered Ti–48Al–8Cr–2Ag nanocrystalline coating was lower than that of the Ti₃Al alloy at 900°C. The former formed a scale of merely Al₂O₃ and the latter formed a scale of TiO₂. However, the Ti–48Al–8Cr–2Ag nanocrystalline coating showed a little bit higher oxidation rate than Ti₃Al alloy at 1000°C, because outer TiO₂ scale formed and columnar boundaries of the coating gave a larger actual oxidation area than the original alloy. The electrochemical corrosion behavior was investigated in 3.5% NaCl solution at room temperature. The coating showed the excellent electrochemical corrosion resistance in 3.5% NaCl solution, because it exhibited stable passive polarization behavior without any overpassivation phenomena.